BRIDGING EXPECTATIONS: SERVICE QUALITY AS A LINK BETWEEN COMPETENCE, TECHNOLOGY, AND STAKEHOLDER SATISFACTION - Choraitun Nisa; Nurul Aisyah Rachmawati (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2026)
Public service is a key pillar in implementing a country's government system. Within the public service system, the State Civil Apparatus (ASN) plays a central role in managing and providing services to the public. Public services offered to the public, especially employers and workers/laborers, include instruments such as Company Regulations (PP) or Collective Labour Agreements (PKB). This study aims to determine how officer competence and technology affect stakeholder satisfaction and service quality, with service quality acting as an intervening factor in Company Regulation and Collective Labour Agreement services. The research employed SEM-PLS analysis. The population consisted of stakeholders managing company regulations and collective labor agreements through the e-PP and e-PKB applications at the Ministry of Manpower, with a sample of 100 respondents. A questionnaire was used as the research instrument. The results indicate that officer competence does not influence stakeholder satisfaction. Conversely, technology implementation and service quality impact stakeholder satisfaction. Additionally, both officer competence and technology implementation influence service quality. Service quality fully mediates the relationship between officer competence and stakeholder satisfaction. It also partially mediates the relationship between technology implementation and stakeholder satisfaction.